Model of Improving Employee Performance Through Self Efficacy and Work Motivation with Organisational Citizenship Behaviour (OCB) as an Intervening Variable at the Demak Regency Transportation Office - Ayu Hestiningtyas Agustya Putri (Jurnal Indonesia Sosial Sains, 2025)
Employee performance plays a crucial role in the success of an organization, including the Demak Regency Transportation Agency. This study aims to examine the direct effects of self-efficacy and work motivation on performance, as well as their influence through OCB as an intervening variable. Using an explanatory research design with a quantitative approach, the study surveyed 85 employees from the Demak Regency Transportation Office using a census method. Data were collected via a Likert-scale questionnaire and analyzed with Partial Least Squares (PLS) through SmartPLS 3. The results revealed that both self-efficacy and work motivation have a positive and significant impact on employee performance. Furthermore, OCB was found to mediate the relationship between self-efficacy, work motivation, and performance. These findings confirm that increasing self-efficacy, work motivation, and OCB can encourage more optimal performance. In conclusion, effective management of self-efficacy, work motivation, and OCB variables can be an important strategy in improving the performance of Demak Regency Transportation Agency employees. This research provides a practical contribution to human resource management in the government sector.